STRATEGI GURU DALAM MENUMBUHKAN SIKAP TOLERANSI MELALUI SISTEM AMONG DALAM PERSEPEKTIF HADIS - Khoiriyah, Zulfatul; Zulkipli Lessy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
An attitude of tolerance is very important in building harmonious relationships between individuals and between groups.  In the educational context, teachers have an important or key role in forming students' attitudes of tolerance.  The among system, which is one of the principles in Islamic teachings, teaches the values of tolerance, mutual respect and justice. The attitude of tolerance is widely explained in the Al-Qur'an and Hadith as the main source of Islamic teachings, providing guidance on how teachers can implement the among system in learning so that students can develop a good attitude of tolerance.  This research uses a descriptive qualitative approach with content analysis to explore teachers' strategies in fostering attitudes of tolerance through the among system.  It is hoped that it can increase a good sense of tolerance.  The results of this research can also contribute to increasing students' understanding of teacher strategies in building students' attitudes of tolerance in the context of Islamic education.  Teachers can also provide in-depth socialization about tolerance, involving all school members in all activities so that mutual respect can emerge.  Keywords: teacher strategy, tolerance attitude, among system